Academic stress and academic performance in students of the national training service in industrial work (Senati) - Pando Tumpay, Angela Antonia (2018)
At present, the academic stress is a problematic that recently they pay attention him, hereby the problem arises which is the relation between the academic stress and the level of academic performance in students of the career of Industrial Administration? The aim was, to determine the relation that exists between the academic stress and the level of academic performance in students of the career of Industrial Administration of the SENATI, the design of investigation is not experimental, transverse, correlacional. The taken sample belongs 99 pupils, shaped by 51 women and 48 males. The results indicate that there exists significant high relation between the variable academic stress and academic performance, likewise there exists significant high relation between the variable reactions.